UKURAN KALSIUM ION DALAM SERUM TOTAL KALSIUM (CALSIUM TOTAL) MENGGUNAKAN BERBAGAI ALAT SWA-ANALISIS (AUTO ANALYSER) - J. Nugraha; Carolina M Viany S; Soehartini B. S. (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Calcium measurements in the emergency laboratory use several instruments. Nova pHox Plus (group A) measures ionized calciumwhereas Beckman Synchron CX5 (group B) and Cobas Integra (group C) measures total calcium. Comparison of the results from the threeauto analysers has never been performed. To compare calcium results using three auto analyzers are Nova pHox Plus, Beckman SynchronCX5, and Cobas Integra. Samples consisting of whole blood were examined by Nova pHox Plus auto analyser and serum samples wereexamined using Beckman Synchron CX5 and Cobas Integra auto analyser. This study has been carried out on 21 individuals. Statisticalanalysis was performed using T-test and Pearson correlation coefficient. The level of significance was determined as 0.05. Results of thethree auto analysers did not show significant correlation (P > 0.05). There were not significant correlation between Nova pHox Plusand Beckman CX5, Cobas Integra.